Pemanfaatan Media Sosial Sebagai Media Pembelajaran Biologi Di Era Digital - Hasanudin, Muhamad (Gunahumas, 2022)
The coronavirus Covid-19 pandemic has shifted Indonesian educational process from face to face lecture to online lecture. The use of various pedagogical technologies as well as communication media are inevitable tools to optimize a meaningful lecture for the sake of students learning experience. The increased intensity of social media use for students has been utilized as an opportunity to make it learning media in Biology during the pandemic. Therefore, this research aimed at exploring the plan, the method and the challenge of social media use as learning media. The plan of social media use as learning media was executed based on the following steps; (a) determining the learning outcomes, (b) preparing leaning materials, and (c) planning the assessment instruments. In addition, the method of social media use as learning media in Indonesian language and literature can be done by giving a structured assignment through some activities such as (a) creating videos, pictures, or infographics and (b) making a writing and reading journal. Furthermore, the challenge faced by lecturers in using social media as learning media was that the lecturers ought to be self-prepared to be a technology literate. Also, they ought to improve their skills and abilities in creative and innovative ways in accordance with the development of technology and science so that they are able to provide an appropriate learning circumstances based on millenial students characteristics.